Pemberdayaan Himpunan Mahasiswa Program Studi (HMPS) Dalam Upaya Mengurangi Jumlah Anak Putus Sekolah Di Pulau-Pulau Kecil Perbatasan - Ratnah Kurniati MA; Asmirani Alam; Sigit Sugiarto; Lestari Lestari; Edy Sony; Sitti Fatimah Kamaruddin; Micael Ririhena; John Nandito Lekitoo; Dian Rubiana Suherman (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
This program aims to reduce the percentage of school dropouts in border islands. Through this program, researchers created an educational environment by involving students of the Study Program Student Association (HMPS). This program was held every Saturday in Wakarleli, Maluku Barat Daya, during October 2023 - November 2023 involving around 20 children in various age categories and around 5-10 students at each meeting. The method used in this activity is descriptive method. The activities supporting the program are educational games which are implemented at the beginning and at the end of the meeting, the introduction of letters and numbers, and counting activities. The results of evaluations and interviews show that this program can increase children's confidence levels, train their communication skills, patience, tolerance, and helping attitudes between children. In addition to the great benefits for the children, this program also provides huge benefits for the students and lecturers involved. For students, this program is considered to increase their creativity in making learning media. Where this skill is a much needed skill, especially for students of the Mathematics Education and PGSD Study Programs. In addition, for students of the Law Study Program, this activity can also foster sensitivity in society and improve their communication skills which are also needed in their future profession. In general, in this program students are trained to work together, socialize and build their confidence to be in public.